Effects of glucocorticoids on vitamin D3-metabolizing 24-hydroxylase (CYP24A1) in Saos-2 cells and primary human osteoblasts. (1st October 2019) - Zayny, Ahmad; Almokhtar, Mokhtar; Wikvall, Kjell; Ljunggren, Östen; Ubhayasekera, Kumari; Bergquist, Jonas; Kibar, Pinar; Norlin, Maria
Abstract: Vitamin D is essential for bone function and deficiency in active vitamin D hormone can lead to bone disorders. Long-term treatment with glucocorticoids results in osteoporosis and increased risk of fractures. Much remains unclear regarding the effects of these compounds in bone cells. In the current study, human osteosarcoma Saos-2 cells and primary human osteoblasts were found to express mRNA for the vitamin D receptor as well as activating and deactivating enzymes in vitamin D3 metabolism. These bone cells exhibited CYP24A1-mediated 24-hydroxylation which is essential for deactivation of the active vitamin form. However, bioactivating vitamin D3 hydroxylase activities could not be detected in either of these cells. Several glucocorticoids, including prednisolone, down regulated CYP24A1 mRNA and CYP24A1-mediated 24-hydroxylase activity in both Saos-2 and primary human osteoblasts. Also, prednisolone significantly suppressed a human CYP24A1 promoter-luciferase reporter gene in Saos-2 cells co-transfected with the glucocorticoid receptor. Thus, the results of the present study show suppression by glucocorticoids on CYP24A1 mRNA, CYP24A1-mediated metabolism and CYP24A1 promoter activity in human osteoblast-like cells. As part of this study we examined if glucocorticoids are formed locally in Saos-2 cells. The experiments indicate formation of 11-deoxycortisol, a steroid with glucocorticoid activity, which can bind the glucocorticoid receptor. Our data showing suppression by glucocorticoids on CYP24A1 expression in human osteoblasts suggest a previously unknown mechanism for effects of glucocorticoids in human bone, where these compounds may interfere with regulation of active vitamin D levels. Highlights: Bone function is affected by vitamin D deficiency and treatment with glucocorticoids. Vitamin D metabolism and effects of glucocorticoids were studied in osteoblasts. Glucocorticoids suppressed CYP24A1, an enzyme that decreases active vitamin D levels. Glucocorticoids may influence bone function via effects on active vitamin D levels.